Kontrak Kerja Konstruksi Pembangunan Gedung GMB Ditinjau Berdasarkan Red Book FIDIC - Freya Beatrice Fredella; Y. Sari Murti Widiyastuti (Fakultas Hukum Universitas Surabaya, 2022)
This study was aimed to study the construction work contract for the construction of the GM Bookstore building between PT NI and UGM if reviewed based on the Red Book Federation Internationale des Ingenieurs Counsels (FIDIC) because GM Bookstore building that should be finished February 2005 still not handed over until 2022. This research was conducted with the normative legal research type by using the secondary data in the form of primary legal materials and secondary legal materials obtained with literature studies and interviews. The data were then analyzed using qualitative analysis methods. Conclusion is drawn using a deductive thinking process. The results and conclusions of this study are The construction work contract for the construction of the GMB building between PT NI and UGM when reviewed based on the Red Book by the Fédération Internationale des Ingénieurs Counsels (FIDIC) is only 4 clauses out of 21 clauses with 7 subclauses from the 168 subclauses of the General Conditions Red Book FIDIC which are included in the contract for the construction of the GM Bookstore building. The sub-clauses that are included in the work contract for the construction of the GM Bookstore building are also used only partially and is not constitute the entire sentence referred to in the sub-clause.